The noel stranger [compact disc, unabridged] - Evans, Richard Paul (Evans, Richard Paul. Noel collection., 2018)
Still reeling from a scandal that ended her marriage, Maggie Walther finds renewal in a relationship with the kind man who owns the local Christmas tree lot and is also starting his life over, but just as she begins to trust him, she discovers a dark secret from his past.